Determination of cobalt in chamomile tea samples at trace levels by flame atomic absorption spectrophotometry after poly(vinyl alcohol)-magnetic hydrogel based dispersive solid phase extraction. Issue 1 (8th December 2022) - Karlıdağ, Nazime Ebrar; Demirel, Rabia; Serbest, Hakan; Turak, Fatma; Bakırdere, Sezgin
Abstract : In this study, an analytical strategy was proposed for the determination of cobalt at trace levels by using a flame atomic absorption spectrophotometry (FAAS) system after magnetic hydrogel based dispersive solid phase extraction (MH-DSPE). Abstract : In this study, an analytical strategy was proposed for the determination of cobalt at trace levels by using a flame atomic absorption spectrophotometry (FAAS) system after magnetic hydrogel based dispersive solid phase extraction (MH-DSPE). Poly(vinyl alcohol) based magnetic hydrogels (PVA-MH) were synthesized easily, quickly, and cost effectively in the laboratory and used as an adsorbent material in the microextraction process. Under the optimum experimental conditions, the limit of detection (LOD) and limit of quantitation (LOQ) values were recorded as 4.2 and 14.1 μg L −1, respectively. To investigate the matrix effects on the analyte signal, spike experiments were performed using chamomile tea extracts and good recovery results were obtained between 85.7 and 113.8%. A 57.8-fold improvement was achieved in the detection power compared to that of a conventional FAAS system. The results obtained throughout all experimental studies demonstrated the applicability in addition to the accuracy of the method for the quantification of trace levels of cobalt with high accuracy in a chamomile tea matrix.